Synergistic anti-icing and snow-melting performance of two-component road markings enabled by PCMs and slow-release salts - Wei Zhang; Kaibo Yang; Renshan Chen; Chong Wang; Xusheng Wei (PLoS ONE, 2026)
Conventional road marking coatings suffer significant performance deterioration under winter conditions, including frost coverage, reduced retroreflectivity, and low-temperature embrittlement. This study presents a functional two-component road marking coating incorporating a composite anti-icing additive composed of a temperature-regulating phase-change material (TH-ME5) and a salt-based slow-release agent (T-SEN). The influence of additive content and the TH-ME5/T-SEN ratio on coating properties, road performance, and ice/snow mitigation was systematically evaluated. Results show that a total additive content of ≤20 wt.% maintains compliance with standard requirements for adhesion, flexibility, wear resistance, drying time, retroreflectivity, hiding power, alkali resistance, and UV aging. Ice adhesion tests reveal a two-stage anti-icing mechanism: TH-ME5 provides latent heat buffering during early freezing, while T-SEN governs long-term deicing. The optimal formulation—20 wt.% additive with a TH-ME5:T-SEN ratio of 1:3—achieved the lowest relative ice adhesion. Snow-melting simulations further demonstrate the coating’s ability to delay ice formation and reduce surface snow accumulation. This PCM–salt synergistic approach provides a feasible and scalable strategy for durable, self-deicing pavement markings in cold regions.